2008
DOI: 10.1002/arch.20232
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 modulates the expression of antimicrobial peptides in the fat body and midgut of Anopheles albimanus

Abstract: Prostaglandins (PGs) participate in the regulation of vertebrate and in at least six insect orders' immune responses. We identified PGE 2 in midgut, fat body, Malpighian tubules, and ovarioles of Anopheles albimanus (Aa) mosquitoes. Our data indicate that PGE 2 synthesis in cultured midguts responds to the presence of two bacterial species, Micrococcus luteus and Klebsiella pneumoniae. The production of mRNA coding for antimicrobial peptides Aa-Attacin, Aa-Cecropin, and Aa-Gambicin was observed in cultured fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…The An. albimanus immune response against microorganisms is mediated by phagocytosis, nodule formation, encapsulation, melanization (including generation of reactive oxygen species), and AMPs (Hernández‐Martínez et al, ; Lanz‐Mendoza et al, ; García Gil de Muñoz et al, ). However, the mechanisms to produce the high amounts of AMP molecules required for effective immune responses still require elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…The An. albimanus immune response against microorganisms is mediated by phagocytosis, nodule formation, encapsulation, melanization (including generation of reactive oxygen species), and AMPs (Hernández‐Martínez et al, ; Lanz‐Mendoza et al, ; García Gil de Muñoz et al, ). However, the mechanisms to produce the high amounts of AMP molecules required for effective immune responses still require elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have implicated PGE2 signaling on the synthesis of antimicrobial peptides (AMPs) in Anopheles albimanus (4). Therefore, we examined the expression of major AMPs in mosquitoes primed with PGE2 or following AgPGE2Rsilencing.…”
Section: Pge2 Biosynthesis and The Influence Of Pge2 Signaling On Mosmentioning
confidence: 98%
“…Eicosanoids are lipid-derived signaling molecules that include prostaglandins (PGs), leukotrienes (LTs), lipoxins (LXAs), and epoxyeicosatrienoic acid (EETs), that serve important roles in immune regulation (1)(2)(3). Evidence suggests that these responses are evolutionally conserved across metazoa, where eicosanoids significantly influence insect cellular immunity (4)(5)(6)(7)(8)(9)(10). In the mosquito, Anopheles gambiae, eicosanoids such as prostaglandin E2 (PGE2) and lipoxins have integral roles in mediating immune priming and mosquito susceptibility to malaria parasite infection (11,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects are reversed by AA treatment, suggesting that eicosanoids modulate this response (Garcia et al 2004a). It was also shown that in Anopheles albimanus , a primary vector for malaria vivax in Mexico, DEX inhibits the expression of mRNAs corresponding to specific antimicrobial peptides (AMPs), such as cecropin, gambicin and attacin (García-Gil-de-Muñoz et al 2008). …”
mentioning
confidence: 99%